Graphene Oxide as a Carbocatalyst for a Diels–Alder Reaction in an Aqueous Medium. Issue 18 (4th September 2017) - Girish, Yarabhally R.; Pandit, Subrata; Pandit, Subhendu; De, Mrinmoy
Abstract: The Diels–Alder (DA) reaction, a [4+2] cycloaddition reaction, is highly important in synthetic organic chemistry and is frequently used in the synthesis of natural products containing six‐membered rings. Herein, we report an efficient protocol for the DA reaction between 9‐hydroxymethylanthracene and N‐substituted maleimides using two‐dimensional graphene oxide (GO) as a heterogeneous carbocatalyst in an aqueous medium at room temperature. High yields, a wide substrate scope, low temperature, excellent functional group tolerance, atom economy, and water as a green solvent are noteworthy features of this protocol. The heterogeneous GO catalyst can be easily recovered and used multiple times without any significant loss in catalytic activity. Abstract : GO, GO, GO ! An efficient protocol for the Diels–Alder reaction between 9‐hydroxymethylanthracene and N‐substituted maleimides has been developed. The method uses two‐dimensional graphene oxide (GO) as a heterogeneous carbocatalyst in an aqueous medium at room temperature. The protocol features high yields, a wide substrate scope, low temperature, excellent functional group tolerance, atom economy, and water as a green solvent.